Genetic variation for yielding and girth increment in progenies of Hevea - de Souza Gonçalvez, Paulo; Bortoletto, Nelson; Lúcio Mello Martins, Antônio; Vitória Cecchetti Gottardi, Maria; Aldo Ortolani, Altino (Pesquisa Agropecuaria Brasileira, 1998)
This paper is a study of genetic variation in half-sib progenies phenotypically selected from clones of rubber trees [Hevea brasiliensis (Willd. ex Adr. de Juss.) Müell. Arg.] of a base-population introduced from Malaysia. The trial took place at the Experimental Station of Votuporanga (São Paulo State - Brazil) under a randomized complete block design with 22 treatments and five replications. The characters studied were: yield following Hamaker-Morris-Mann (HMM) conducted at 40, 43 and 46 months of age, and girth increment evaluated at 12, 24, 36 and 48 months of age. Results indicated significative differences for different ages evaluated for both characters. Progenies x ages interaction was significant only for girth increment. The estimates of the different types of heritabilities were greater for girth increment. Heritabilities in the restricted sense, estimated at plant level, were greater than those obtained by plants within progenies, indicating selection response perspectives of these characters and revealing the possibility for success in selection within ages for tests of production and girth increment.